TRANSFORMING THE HEALTH OF THE ELDERLY THROUGH THE COMBINATION OF HATHA YOGA AND CHAYOTE JUICE FOR MENTAL HEALTH AND BLOOD PRESSURE - Nurul Imam; Shinta Wurdiana Rhomadona; Nasywa Benita Trismantoro; Savira Agustina (Universitas Kadiri, 2025)
Hypertension in the elderly is still a serious health problem, especially in the Surabaya area with the highest prevalence in East Java. This condition not only affects the physical, but also has an impact on the mental health of the elderly, such as anxiety and depression, which often go unnoticed and actually worsen blood pressure. This study aims to examine the effectiveness of the combination of Hatha Yoga therapy and chayote juice in lowering blood pressure and improving the psychological condition of the elderly. The research design used a quasi-experiment with a pre-post test approach in two groups. A total of 100 elderly hypertensive patients in RW 04, Sumber Rejo Village, Surabaya, were divided into treatment groups (n=50) and control groups (n=50) through purposive sampling techniques. The treatment group underwent Hatha Yoga and consumed chayote juice twice a week for four weeks. Meanwhile, the control group participated in routine elderly gymnastics. Data were collected through questionnaires and observations, then analyzed using Wilcoxon and Mann-Whitney tests. The results showed a significant improvement in the emotional aspects of the elderly and a marked decrease in blood pressure in the treatment group with significant difference results (p = 0.000). This combination therapy has been shown to be effective and can be recommended as a safe, easy-to-apply, and beneficial nursing intervention in treating hypertension and mild psychological disorders in the elderly. Keywords: Hypertension, Elderly, Mental Health, Hatha Yoga, Chayote.